Intelligent Zero Trust Enterprise Systems Using Machine Learning DevOps Automation Federated Analytics and Secure Microservices Infrastructure (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
The rapid digital transformation of enterprises across finance, healthcare, manufacturing, education, and government sectors has expanded the attack surface and increased cyber risk exposure. Traditional perimeter-based security models are insufficient in protecting distributed cloud-native ecosystems. Intelligent Zero Trust Enterprise Systems integrate Zero Trust Architecture (ZTA), Machine Learning (ML), DevOps automation, Federated Analytics, and Secure Microservices Infrastructure to build adaptive, resilient, and self-healing digital platforms. This research presents a comprehensive framework that combines identity-centric access control, continuous verification, behavior analytics, AI-driven anomaly detection, automated CI/CD security enforcement, and privacy-preserving federated learning to enhance enterprise cyber resilience. The study proposes an architecture that leverages containerization, service mesh security, API governance, encrypted communication, and policy-as-code enforcement to enable secure, scalable operations. The integration of ML-based risk scoring with DevSecOps automation ensures real-time threat detection and rapid response while maintaining regulatory compliance. Federated analytics further enables distributed intelligence without compromising data sovereignty. The proposed methodology demonstrates how enterprises can transition from static defense mechanisms to dynamic, intelligent security ecosystems. This paper contributes a structured model, implementation roadmap, and evaluation strategy for next-generation secure enterprise systems.
Keywords: Zero Trust Architecture; Machine Learning Security; DevSecOps; Federated Learning; Microservices Security; Cloud-Native Architecture; Identity and Access Management; Continuous Authentication; Secure API Gateway; Behavioral Analytics; Cyber Resilience; Enterprise Security Automation